2006
DOI: 10.1002/mrm.20866
|View full text |Cite
|
Sign up to set email alerts
|

In vivo quantitative three‐dimensional motion mapping of the murine myocardium with PC‐MRI at 17.6 T

Abstract: This work presents a method that allows for the assessment of 3D murine myocardial motion in vivo at microscopic resolution. Phase-contrast (PC) magnetic resonance imaging (MRI) at 17.6 T was applied to map myocardial motion in healthy mice along three gradient directions. High-resolution velocity maps were acquired at three different levels in the murine myocardium with an in-plane resolution of 98 m, a slice thickness of 0.6 mm, and a temporal resolution of 6 ms. The applied PC-MRI method was validated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
31
0
Order By: Relevance
“…Data acquisition was gated to occur during systole (i.e., when blood flow velocity is at a maximum) such that excited, fast flowing blood is not refocused during acquisition and thereby generating images with black blood contrast. Next, blood flow measurements were made in a single slice location through the ascending aorta using data generated with a phase-contrast cine (PC-cine) method consisting of a velocity compensated FLASH sequence [24]. To quantify blood flow velocity, data sets of ∼34 cine frames over one period of the cardiac cycle were acquired under three encoding conditions: two with flow-encoding and one completely flow compensated.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…Data acquisition was gated to occur during systole (i.e., when blood flow velocity is at a maximum) such that excited, fast flowing blood is not refocused during acquisition and thereby generating images with black blood contrast. Next, blood flow measurements were made in a single slice location through the ascending aorta using data generated with a phase-contrast cine (PC-cine) method consisting of a velocity compensated FLASH sequence [24]. To quantify blood flow velocity, data sets of ∼34 cine frames over one period of the cardiac cycle were acquired under three encoding conditions: two with flow-encoding and one completely flow compensated.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…40 Further development of phase contrast MRI to produce multi-slice cine images involves an electrocardiogram synchronized time-resolved framework to allow assessment of blood-flow characteristics with high spatial and temporal resolution of a cardiovascular region of interest. 30,74 Sometimes there may be poor quality image registration due to poor respiratory control during scanning. Usually a ghosting artefact 4,41,70 appears on the images.…”
Section: Comparison Of Pc-mri With Ultrasoundmentioning
confidence: 99%
“…The downtrades are greater field inhomogeneity and susceptibility to artifacts and higher radiofrequency (RF) power deposition in tissue-measured by the specific absorption rate (SAR) [101]. Overall, although some authors report nice image acquisitions at clinical field strength (1.5-3 T) with optimized coils [29,53,62], or at the very high field of 17.6 T [60,61], it is generally admitted that the range of 7-11.7 T offers the best trade off for most applications in small animals [48]. Systems can be either horizontally or vertically mounted.…”
Section: Technical Considerationsmentioning
confidence: 97%
“…Different studies have successfully determined myocardial velocities in mice at different time point of cardiac cycles using this technique. If first studies were using bright blood contrast [60,105,134], blood suppression has been shown to improve accuracy of measurements in further developments [43,79]. Baseline values of normal transmural wall motion pattern have been carefully established with TPM, allowing further comparison with genetically and surgically manipulated mouse models [43].…”
Section: Tissue Phase Mapping (Tpm)mentioning
confidence: 99%